Fetal origins—A life cycle model of health and aging from conception to death - Carl-Johan Dalgaard; Casper Worm Hansen; Holger Strulik (Health Economics, 2021)
The fetal origins hypothesis suggests that health and nutrition shocks in utero are causally related to health deficits in old age. It has received considerable empirical support, both within epidemiology and economics but so far it has not been integrated into a life cycle theory of human aging and longevity. The present study shows that the health deficit model, based on the frailty index developed in gerontology, generates shock amplification consistent with the hypothesis. In order to discuss human health over the life cycle from conception to death, we develop a theory of ontogenetic growth and health in utero and during childhood, unify it with the health deficit model of adult aging, and discuss the transmission of early-life shocks to late-life health deficit accumulation.
Keywords: 330; fetal origins; health deficits; in utero development; ontogenetic growth